Partial Oxidation as a Rational Approach to Kinetic Control in Bioinspired Magnetite Synthesis. Issue 16 (4th March 2015) - Altan, Cem L.; Lenders, Jos J. M.; Bomans, Paul H. H.; de With, Gijsbertus; Friedrich, Heiner; Bucak, Seyda; Sommerdijk, Nico A. J. M.
Abstract Biological systems show impressive control over the shape, size and organization of mineral structures, which often leads to advanced physical properties that are tuned to the function of these materials. Such control is also found in magnetotactic bacteria, which produce—in aqueous medium and at room temperature—magnetite nanoparticles with precisely controlled morphologies and sizes that are generally only accessible in synthetic systems with the use of organic solvents and/or the use of high‐temperature methods. The synthesis of magnetite under biomimetic conditions, that is, in water and at room temperature and using polymeric additives as control agents, is of interest as a green production method for magnetic nanoparticles. Inspired by the process of magnetite biomineralization, a rational approach is taken by the use of a solid precursor for the synthesis of magnetite nanoparticles. The conversion of a ferrous hydroxide precursor, which we demonstrate with cryo‐TEM and low‐dose electron diffraction, is used to achieve control over the solution supersaturation such that crystal growth can be regulated through the interaction with poly‐(α, β)‐dl‐aspartic acid, a soluble, negatively charged polymer. In this way, stable suspensions of nanocrystals are achieved that show remanence and coercivity at the size limit of superparamagnetism, and which are able to align their magnetic moments forming strings in solution as is demonstrated by cryo‐electron tomography.